Compreendendo a experiência de pessoas portadoras de transtorno mental: histórias de vidas severinas repletas de possibilidades - Marcelino, Cristiane Maria Diógenes Nunes (2007)
This study aims to understand the experience of people suffering from mental disorder. The patients are enrolled in a mental health ambulatory clinic in the city of Natal (RN). Mental disorders are growing rapidly in the contemporary world and are a source of intense mental suffering. Besides patients being strongly marked by a history of isolation and prejudice, they have been the target of real atrocities committed in the name of preservation of a supposed normality. The understanding and treatment of this disorder is influenced by cultural and historical inferences, depending on the period in which it is experienced. Semi-directed Interviews were conducted with a group of users, with the emphasis on giving voice to their uniqueness and individuality, highlighting how each one perceives his or her own experience. These were recorded and later transcribed by identifying the core of meanings. The results were analyzed under the gaze of the Humanist Phenomenology Existential perspective, which aims to unravel the phenomenon, without truths from volatility, highlighting the existence of the mental disorder as a way of living, being permeated by suffering mental and influenced by social problems, assuming contours very particular to each individual. Some progress has been perceived, even by users, with respect to the change of paradigm in the way of care, but still there is a consistent emphasis on medical and drug use. The changes point to the need for offering services to replace the asylum hospital model, and in addition to accept the bearer of mental disorder as a citizen, a bearer of rights who should be accepted and respected by society. Despite the pain expressed and its close liaison with suicide, their reports are full of perspectives and attitudes of confrontation facing life, pointing to new possibilities to be, recreating itself